Gestión de Talento Humano en Disensa Distribuidora Touma de la Ciudad de Babahoyo, periodo 2023. - Piza Tierra, Christopher Alejandro (2024)
The research based on a case study was carried out at the company Disensa Distribuidora Touma in the city of Babahoyo. The research covers the variable of human talent management, because it is very important to pay attention to the processes used to incorporate people to work for the company. The objective of the research was to analyze the Human Talent Management at Disensa Distribuidora Touma in the city of Babahoyo for the period 2023, applying research techniques that allow the improvement of the work environment. To fulfill this purpose, a descriptive methodology design was used, supported by the deductive and inductive method, the survey applied to the staff and the interview with the manager were used. As a result, it was obtained that there is an acceptable management of human talent, where processes such as recruitment and selection of personnel are prioritized, 20% of the staff does not have access to training, so it is recommended that a comprehensive plan be structured that benefits all workers. The line of research was: Financial, administrative, tax, audit and control management, and is also part of the research subline: Public and private companies and institutions, being closely linked to the research carried out.